IMPLEMENTASI KURIKULUM 2013 DALAM KEGIATAN PEMBELAJARAN FIQH KELAS IV DI MI SALAFIYAH DAN MI BUSTANUL MUTA’ALIM KABUPATEN GROBOGAN TAHUN PELAJARAN 2018/2019 - Ahmad Syaiful Bahri (Jurnal Studi Islam dan Sosial, 2019)
Implementation of 2013 Curriculum in Class IV Fiqh Learning Activities in MI Salafiyah and MI Bustanul Muta’alim Grobogan Regency Academic Year 2018/2019. Thesis of Islamic Religious Education Study Program (PAI), Postgraduate Program, Salatiga State Islamic Institute, Advisor Dr. Mukh Nursikin, M.Sc. This study aims to describe how the implementation of the 2013 curriculum in class IV Fiqh learning in MI Salafiyah Grobogan Regency and MI Bustanul Muta’alim Grobogan Regency using the 2013 curriculum. Curriculum implementation components discussed include: (1) learning planning, (2) learning activities, (3) evaluation of learning activities. This research approach uses a qualitative approach while the type of this research is a qualitative descriptive study. Description of research data on the Implementation of the 2013 Curriculum Learning in MI Salafiyah and MI Bustanul Muta'alim that the fourth grade Fiqh Teacher has carried out learning properly according to the prepared lesson plans. In general, the stages of learning implementation are initial or preliminary activities, core and closing activities. In the core activities, the teacher applies a scientific approach including observing, asking, trying, reasoning and communicating The results of the study The implementation of learning is presented with Learning Evaluation Results by applying the 2013 curriculum. The implementation of learning takes place well in accordance with the 2013 curriculum. Thus, the school has been able to implement the 2013 curriculum with modest learning media, but teachers who have high leadership will achieve success in implementing the 2013 curriculum in student learning in class.